2008
DOI: 10.1345/aph.1k655
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids for Prevention of Postextubation Laryngeal Edema in Adults

Abstract: Data from the most recent well-designed clinical trials suggest that prophylactic corticosteroid therapy can reduce the incidence of PELE and the subsequent need for reintubation in mechanically ventilated patients at high-risk for PELE. Based on this information, clinicians should consider initiating prophylactic corticosteroid therapy in this population. Further studies are needed to establish the optimal dosing regimens as well as the subgroups of patients at high risk for PELE who will derive the greatest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…22 Previous published systematic reviews focusing on the preventive and therapeutic effect of steroids in different age groups showed no clear benefit on the occurrence of airway complications in adults, but our updated results do show such a benefit. [4][5][6] A recent meta-analysis 10 found no clear effect of steroids on preventing laryngeal oedema after extubation and reintubation in adults.…”
Section: Strengths and Limitationsmentioning
confidence: 43%
See 1 more Smart Citation
“…22 Previous published systematic reviews focusing on the preventive and therapeutic effect of steroids in different age groups showed no clear benefit on the occurrence of airway complications in adults, but our updated results do show such a benefit. [4][5][6] A recent meta-analysis 10 found no clear effect of steroids on preventing laryngeal oedema after extubation and reintubation in adults.…”
Section: Strengths and Limitationsmentioning
confidence: 43%
“…Administration of steroids before selected extubation is assumed to protect against or treat mucosal oedema in the glottic region caused by pressure or irritation from the endotracheal tube. Roberts et al compared trials published after 2000 with older studies 22 and suggested that the lack of clinical benefit observed with earlier studies might have resulted from lower total steroid doses. These authors also pointed out that older studies generally used only a single dose of steroids and suggested that this, compared with the longer duration of treatment in newer studies, might account for the different conclusions.…”
Section: Researchmentioning
confidence: 99%
“…Fan and colleagues calculated a risk reduction of 0.19 (-0.24 to -0.15; number needed to treat, 5) on the occurrence of laryngeal edema and of 0.04 (-0.07 to -0.02; number needed to treat, 25) on the rate of reintubation [16]. On the contrary, the effect of a single-dose regimen used in older studies was not statistically significant in two meta-analyses [16,44]. The benefit from steroids will be greater in patients at risk for laryngeal edema, who could be identified with a positive cuff leak test [42].…”
Section: Preventionmentioning
confidence: 99%
“…We believe it would be wise to monitor such patients on an ICU for at least 2 days. Regular intravenous steroids until tracheal tube removal could substantially reduce the incidence of post-extubation laryngeal oedema and the need for re-intubation in ICU patients ventilated for more than 36 hours [8,9].…”
Section: Discussionmentioning
confidence: 99%